Heritage education and augmented reality: what prospects - Panciroli, Chiara; Macauda, Anita (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2018)
Several national and international researches report relevant aspects about the application of augmented reality in formal and non-formal educational contexts. In fact the augmented reality takes on a meaningful role in relationship between technologies and learning; its applications support an augmented learning, through the reproduction of specific scenarios which go beyond the theoretical dimension. In particular, this contribution aims to propose a reflection on the relationship between heritage education and augmented reality technologies in reference to a collaborative and shared construction of knowledge on heritage.